Do Norwegian Sami and non-indigenous individuals understand questions about mental health similarly? A SAMINOR 2 study. Issue 1 (1st January 2018) - Sørlie, Tore; Hansen, Ketil Lenert; Friborg, Oddgeir
ABSTRACT: The Western culturally developed Hopkins Symptom Checklist (HSCL-10) is a self-report measure of mental distress widely used for both clinical and epidemiological purposes – also in the multiethnic epidemiological SAMINOR studies in Northern Norway, but without any proper cross-cultural validation. Our objective was to test invariance of the HSCL-10 measurements among Sami and the non-indigenous majority population in Northern Norway (participants in the SAMINOR 2 study) and whether the previously used HSCL-10 cut-off level (1.85) fits the Sami subgroups in the study. Participants belonged to Sami core, Sami affiliation, Sami background or majority Norwegian groups. The confirmatory factor analysis framework adapted for testing of measurement invariance showed no significant measurement invariance between the groups indicating that the HSCL-10 response scale predominantly was used in the same way and that significantly different meanings were not ascribed to the same set of questions. The cut-off criteria of 1.85 as indicative of psychological distress based on Norwegian data equal a score of 1.89, 1.94 and 1.91 in the Sami core, Sami affiliation and Sami background groups, respectively. Thus, the same cut-off criterion 1.85 may be safely used in all groups. However, one should still be looking for culture-specific expressions of mental stress.